Effect of Previous Incubation of Aeromonas hydrophila in Wastewater Prior to Its Transfer Into Marine Water Microcosms - Mejri, Selma; Bour, Monia.; Boukef, Imen; Mraouna, Radhia; Boudabbous, Abdeltif (Revue des sciences de l'eau / Journal of Water Science, 2008)
AbstractThe occurrence of the mesophilic motile Gram negative non enterobacterial species A. hydrophila in the wild is a major problem that deserves to be resolved since it is a potentially pathogen able to enter into a non-culturable state on routine bacteriological plating media. These non-culturable forms can be detected by several direct or indirect visualization methods. This species has frequently been isolated from pathological forms in fish farming marine areas, especially near wastewater discharges. Consequently, we studied A. hydrophila in marine water microcosms placed during a 24 hour period in treated waste waters and compared with the homologous strain not placed in the same conditions. Thus, two kinds of microcosms were prepared using filtered and autoclaved marine water or waste water, inoculated by A. hydrophila and maintained at 25°C in darkness. The results obtained indicated that A. hydrophila population incubated at 25°C in marine water declined rapidly (3.21 log units in plate count number) during the first three days. Additionally, we noted that A. hydrophila incubated in marine water after a previous treatment in waste water declined progressively to 2.74 log units (in plate count number). Nevertheless, we showed no significant variations of the number of total bacterial cells for A. hydrophila developed in marine water after prior treatment in waste water, despite the appearance of the VBNC form. During this state, rods of normal size, elongated cells and cocci were obtained. Concomitantly, we determined several changes in biochemical and antimicrobial patterns of stressed A. hydrophila, notably the acquisition of adipate metabolization and an increase of resistance to antimicrobial compounds, especially for A. hydrophila incubated in marine water after treatment in waste water.